Causes of excessive late death after trauma compared with a matched control cohort. Issue 10 (28th July 2016) - Eriksson, M; Brattström, O; Larsson, E; Oldner, A
Abstract: Background: Studies on mortality following trauma have been restricted mainly to in-hospital or 30-day death. Mortality risk may be sustained several years after trauma, but the causes of late death have not been elucidated. The aim was to investigate mortality and analyse causes of late death after trauma. Methods: All injured patients from a regional trauma registry with long-term follow-up were matched in a 1 : 5 ratio with uninjured controls by age, sex and municipality. By linkage to national registries, long-term mortality, causes of death and co-morbidity status were identified. Excess mortality was examined by calculating the all-cause mortality rate ratio (MRR). Results: Among the trauma cohort of 7382 patients, 662 (9·0 per cent) died within 3 years after the index trauma; the 30-day mortality rate was 5·0 per cent. Compared with the control group (36 759 individuals), there was a sustained increase in mortality up to 3 years after trauma; the MRR was 2·88 (95 per cent c.i. 2·37 to 3·50) for days 31–365, 1·59 (1·24 to 2·04) for years 1–2 and 1·43 (1·06 to 1·92) for years 2–3. External causes, including new trauma, were far more common causes of late death in injured patients than in matched controls. Conclusion: Postinjury mortality is increased for several years after trauma. Excess mortality is largely attributed to recurrent trauma and other external causes of death. Abstract : Mortality sustained for years